Ethics of Knowledge Sharing: A Perspective of Social Ontology - Panda, Ranjan K. (ETHICS IN PROGRESS, 2012)
In the contemporary socio-economical scenario, knowledge sharing has become a crucial topic for discussion. As the economy of the societies becoming knowledge centric, knowledge production and dissemination by the educational and other social institutions must play an important role. In this paper, we discuss the notion of knowledge sharing as normative action involving two modes of function: voluntary and obligatory. Knowledge sharing as voluntary action presupposes personal ontology of knowledge. The knower as owner of knowledge has the right to disseminate knowledge. The reason of this dissemination could be sometimes to fulfill certain psychological desire or material needs, rather than purely value centric. Such a mode of sharing could be the reason for the degeneration of knowledge. It is because voluntary dissemination of knowledge does not go beyond the whims and fancies of the knower. On the other hand, knowledge sharing as an obligatory action emphasizes care and commitment. These normative elements could not only transform the attitude of the knower, but also help him to transcend the mere economic and psychological reasons of knowledge sharing. This transcendental logic of sharing would show how knowledge obtains its social ontology.